Question Number 126635 by BHOOPENDRA last updated on 22/Dec/20
Answered by Ar Brandon last updated on 22/Dec/20
$$\mathrm{x}^{\mathrm{2}} +\mathrm{y}^{\mathrm{2}} +\mathrm{z}^{\mathrm{2}} =\mathrm{r}^{\mathrm{2}} \mathrm{cos}^{\mathrm{2}} \theta\mathrm{cos}^{\mathrm{2}} \phi+\mathrm{r}^{\mathrm{2}} \mathrm{cos}^{\mathrm{2}} \theta\mathrm{sin}^{\mathrm{2}} \phi+\mathrm{r}^{\mathrm{2}} \mathrm{sin}\theta \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\mathrm{r}^{\mathrm{2}} \left[\mathrm{cos}^{\mathrm{2}} \theta\underset{\mathrm{1}} {\underbrace{\left(\mathrm{cos}^{\mathrm{2}} \phi+\mathrm{sin}^{\mathrm{2}} \phi\right)}}+\mathrm{sin}^{\mathrm{2}} \theta\right] \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\mathrm{r}^{\mathrm{2}} \left[\mathrm{cos}^{\mathrm{2}} \theta+\mathrm{sin}^{\mathrm{2}} \theta\right]=\mathrm{r}^{\mathrm{2}} \\ $$$${w}\left({x},{y},{z}\right)={f}\left({x}^{\mathrm{2}} +{y}^{\mathrm{2}} +{z}^{\mathrm{2}} \right)={f}\left({r}^{\mathrm{2}} \right) \\ $$$$\frac{\partial{w}}{\partial\theta}=\frac{\partial{f}\left({r}^{\mathrm{2}} \right)}{\partial\theta}=\mathrm{0}=\frac{\partial{w}}{\partial\phi} \\ $$